U.S. Geological Survey Polar Bear Mark-Recapture Records, Alaska Portion of the Southern Beaufort Sea, 2001-2010 - U.S. Geological Survey, Alaska Science Center Polar Bear Research Program (USGS Science Data Catalog, 2015)
These data were collected by the U.S. Geological Survey, Alaska Science Center, Polar Bear Research Program as part of long-term research on the southern Beaufort Sea polar bear population.